Comparative analysis of yak milk and bovine milk glycoprotein N/O-glycome by online HILIC-UV-ESI-MS/MS. (15th February 2022) - Yang, Yuerong; Lu, Yu; Liu, Yinchuan; Pan, Yu; Ma, Hongjuan; Huang, Linjuan; Wang, Zhongfu
Abstract: Yak milk (YM) has higher protein content than other bovine milk (BM) varieties. The bioactivity of milk glycoproteins is related to N / O -glycans. We qualitatively and quantitatively compared the N / O -glycome of YM and BM glycoproteins using stable isotope labeling combined with hydrophilic interaction chromatography and electrospray ionization mass spectrometry. We identified 79 and 78  N -glycans in YM and BM, respectively. Two N -glycans (H4N5F1A1; H5N4F1) were exclusive to YM. The content ratios of different types of N -glycans differed significantly between YM and BM, with sialylated N -glycans 2.33 times more abundant in YM. Five and seven O -glycans were detected in YM and BM, respectively. Two O -glycans (H1N2; H1N2A1) were exclusive to BM. The bi-sialylated O -glycan, H1N1A2, accounted for 56.1% of O -glycans in YM; it was 5.97 times more abundant in YM than in BM (equal volume basis). This study provides a theoretical basis for the future utilization of YM as a functional food. Graphical abstract: Unlabelled Image